2019
DOI: 10.3390/ijms20123083
|View full text |Cite
|
Sign up to set email alerts
|

Proteolytic Rafts for Improving Intraparenchymal Migration of Minimally Invasively Administered Hydrogel-Embedded Stem Cells

Abstract: The physiological spaces (lateral ventricles, intrathecal space) or pathological cavities (stroke lesion, syringomyelia) may serve as an attractive gateway for minimally invasive deployment of stem cells. Embedding stem cells in injectable scaffolds is essential when transplanting into the body cavities as they secure favorable microenvironment and keep cells localized, thereby preventing sedimentation. However, the limited migration of transplanted cells from scaffold to the host tissue is still a major obsta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 30 publications
0
7
0
Order By: Relevance
“…One developing approach to reduce such limitations is through enzyme immobilization. In particular, enzyme immobilization is seen as a viable means to provide greater user controllability through specific localization strategies and control of enzymes’ catalytic activity using physical [ 66 ] or chemical [ 67 ] bounding to or within synthetic platforms including but not limited to hydrogels [ 17 , 18 , 19 , 20 ], particles [ 15 , 16 , 22 ], nanotubes [ 23 ], or frameworks [ 66 ]. Meanwhile, the recyclability of enzymes can also increase through such immobilization approaches, thus resulting in their repeatable use and reduction in application costs [ 66 ].…”
Section: Challenges and Perspectives For Enzymes Applications: A Case Study Of Enzymes Integration In Biomedical Engineeringmentioning
confidence: 99%
See 2 more Smart Citations
“…One developing approach to reduce such limitations is through enzyme immobilization. In particular, enzyme immobilization is seen as a viable means to provide greater user controllability through specific localization strategies and control of enzymes’ catalytic activity using physical [ 66 ] or chemical [ 67 ] bounding to or within synthetic platforms including but not limited to hydrogels [ 17 , 18 , 19 , 20 ], particles [ 15 , 16 , 22 ], nanotubes [ 23 ], or frameworks [ 66 ]. Meanwhile, the recyclability of enzymes can also increase through such immobilization approaches, thus resulting in their repeatable use and reduction in application costs [ 66 ].…”
Section: Challenges and Perspectives For Enzymes Applications: A Case Study Of Enzymes Integration In Biomedical Engineeringmentioning
confidence: 99%
“…A biocompatible scaffold hydrogel was developed using HA to successfully immobilize active trypsin and collagenase enzymes in a matrix of stem cells to help assist with migration of healing-promoting cells. Glial progenitors (GPs) and mesenchymal stem cells (MSCs) served as examples, with transgenic mice being used as model systems [ 19 ]. Analysis showed that the activity and viability of the HA-enzyme hydrogels were 60 and 28% of that of free enzyme activity, respectively, and that stem cells embedded in the HA-enzyme matrices also retained their survivability.…”
Section: Challenges and Perspectives For Enzymes Applications: A Case Study Of Enzymes Integration In Biomedical Engineeringmentioning
confidence: 99%
See 1 more Smart Citation
“…Physiological and pathological cavities, such as lateral ventricles and stroke lesions, may act as a viable gateway for developing stem cells. Hyaluron, a naturally occurring polymer, can function along with enzymes as an approach to dissolve the connective tissue that acts as a barrier between the scaffold and the host, thus resolving the limited migration of transplanted cells [ 187 ]. Additionally, hyaluronic acid and methylcellulose hydrogels demonstrated improved survival and integration of stem cells [ 188 , 189 ].…”
Section: Remodeling Of the Stroke Tissue Microenvironment Within The Brainmentioning
confidence: 99%
“…To examine impairment and recovery, we utilized a catwalk test to examine gross motor gait, a pasta matrix reach task to assess fine-motor skills (feeding and coordination) and a foot fault task to examine coordination and gait. An emerging strategy in stroke therapy is the direct application of treatments to the stroke lesion [24][25][26]. Accordingly, we mixed PbTx-2 in a hydrogel composed of thiol-modified hyaluronan and polyethylene glycol diacrylate and this composite was deposited epicortically directly above the stroke cavity.…”
Section: Introductionmentioning
confidence: 99%